DIGITAL STUDENT WORKSHEET BASED ON PROJECT-BASED LEARNING INTEGRATED WITH NGADA LOCAL WISDOM FOR NATURAL SCIENCE MATERIAL IN JUNIOR HIGH SCHOOL - Zae, Maria Fridolin; Dinatha, Ngurah Mahendra; Dolo, Fransiskus Xaverius; Kua, Maria Yuliana (STKIP Citra Bakti, 2026)
The problem in this study is that the learning process is generally still conventional, with the dominance of lecture methods and the use of printed Student Worksheet which is less interactive and has not been linked to existing local wisdom. This study aims to develop and test the feasibility of digital Student Worksheet based on Project Based Learning integrated with Ngada local wisdom on additive material for students of SMPS PGRI Bajawa. The method used is research and development or often called R&D (Research and Development) with the model developed is the ADDIE model. The research subjects were 20 students of class lX SMPS PGRI Bajawa. The data collection techniques used were interviews, questionnaires, and expert validation sheets. These data collection techniques allowed for comprehensive data collection to evaluate and develop digital student worksheets based on project-based learning integrated with local Ngada wisdom. in science learning at SMPS PGRI Bajawa. The data analysis techniques used by researchers in this study are qualitative and quantitative data used to obtain research data. Based on the scores the validity of the three experts was 3.94, which is in the very valid criteria. The practicality test for teacher responses was 97.91%, and student responses were 98.13%.